1973
DOI: 10.1002/bip.1973.360120816
|View full text |Cite
|
Sign up to set email alerts
|

Infinite‐dilution viscoelastic properties of poly‐γ‐benzyl‐L‐glutamate in helicogenic solvents

Abstract: synopsisThe storage and loss shear moduli, G , and G", have been measured for solutions of three samples of poly-y-benzyl-L-glutamate with molecular weights from 16 to 57 X lo4, by use of the Birnboim-Schrag multiple-lumped resonator. The frequency range was 106 to 6060 Hz, the concentration range 0.0015-0.005 g/ml, and the temperature 25OC. Two helicogenic solvents with widely different viscosities, dimethylformamide and m-cresol, were used to provide a broader effective frequency range. The intrinsic moduli,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 15 publications
2
54
0
Order By: Relevance
“…The yield stress,  0 obtained from the flow curves showed a power-law dependence on clay concentration which is illustrated in Fig. 1b and this data could be correlated to concentration through 0~c The aforementioned expression is interpreted as originating from a superposition of several Debye relaxations 22,23 . The mean relaxation time is given by  cc .…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…The yield stress,  0 obtained from the flow curves showed a power-law dependence on clay concentration which is illustrated in Fig. 1b and this data could be correlated to concentration through 0~c The aforementioned expression is interpreted as originating from a superposition of several Debye relaxations 22,23 . The mean relaxation time is given by  cc .…”
mentioning
confidence: 78%
“…Such phases possess a relaxation time spectrum as mentioned earlier. Previous works showed that plotting the two components of dynamic viscoelastic characteristics (modulus or viscosity) against each other yields an arc shaped curve if the process can be depicted with a single relaxation time [21][22][23][24][25][26] . The arc transforms to a semicircle or a skewed semicircle if the material owns a distribution of relaxation times 23,24 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…whose spacings correspond to the ratios given by the Zimm theory (13,14). This specifies (9) (10) where Z' and Z" are the reduced intrinsic moduli given by Eqs.…”
Section: Theorymentioning
confidence: 99%
“…8 and 11, Wada (21) obtained the convenient equation (13) and, if 'F can be identified with T 1 of the hybrid spectrum, we calculate for paramyosin B = 4.0 x 10-19 dyn/cm 2 at 20°C. For poly(y-benzyl-L-glutamate), Wada calculated 5 x 10-19 dyn/cm 2 from persistence length data.…”
Section: Rigid Elongated Macromoleculesmentioning
confidence: 99%